Pengaruh Online Customer Rating dan Metode Pembayaran COD terhadap Keputusan Pembelian pada Aplikasi Tokopedia - Erna Nur Ifah; Rachmat Ramadhani; Sarmin Sarmin (International Forum of Researchers and Lecturers, 2024)
The existence of online customer ratings, and COD payment services are expected to be able to influence purchasing decisions. The purpose of this study is to determine and analyze the influence of Online customer ratings on purchasing decisions, the influence of the COD Payment Method on purchasing decisions, on the Tokopedia application. The method used in this study is a quantitative method with a sampling technique using purposive sampling by taking respondent data according to the specified criteria, namely having used the Tokopedia application, the research sampling method using the questionnaire data collection method, using multiple regression analysis and hypothesis testing with IBM SPSS version 25.0. The results of the study showed that there was a positive and significant partial influence of online customer ratings (X1) on purchasing decisions (Y), namely 6,000> 1,985 with a significance value of 0.00 <0.05. The COD payment method (X2) partially had a significant effect on purchasing decisions (Y) on the Tokopedia application, namely 3.803> ttable 1.985 and a significance value of 0.00 <0.05. And simultaneous testing also has an influence between Online customer rating and COD payment method on purchasing decisions, namely the F count value of 36.453> F table 3.09 and a significance value of 0.00 <0.05, meaning that the independent variables of online customer rating and COD payment method simultaneously have a significant effect on the dependent variable of Purchasing Decisions.